Online Shopping among Higher Education Students in Indore: A Factor Analysis Approach - Sharma, Shraddha; Sitlani, Manish (Indian Journal of Marketing, 2013)
The internet, one of the biggest discoveries of the modern era, has transformed and revolutionized processes and procedures of the business world as well. The growing use of the internet in India has created a basis for tremendous prospects for marketers of today and tomorrow. The customers and consumers of modern times are techno savvy and innovative in their attitude. So, the internet is sure to takeover as the prime marketing and selling channel. Thus, it is imperative for the companies to investigate and understand the factors that influence the decision to purchase online. Drawing a sample of 200 higher-education students from Indore, this paper has attempted to explore the various factors that may influence the decision to shop online. The results of the study revealed that Internet Traits, Attitudinal Traits and Convenience significantly affect online shopping behavior of young students, while Perceived Risk in terms of financial risk, privacy, security and product guarantee/warrantee hinders the young students to shop online.